The Oxford handbook of the Indian economy in the 21st century: understanding the inherent dynamism - Goyal, Ashima (Oxford Univ. Press, 2014)
Structure and reform -- The macroeconomy -- The open economy -- Inclusion: equality and opportunity -- Governance -- Infrastructure -- Sectors -- Factors: technology, labour, finance
Enth. 33 Beitr
Keywords: 1960-2012; India -- Economic policy -- 21st century; India -- Economic conditions -- 1991-; India -- Economic policy -- 1991-; Handbuch; Aufsatzsammlung; Geschichte 1900-2000; Wirtschaftsentwicklung; Indien